(untitled) (International journal of artificial intelligence, 2025)
The toponyms of Darband, Akqotal and Iron gate are comprehensively analyzed in the article. During the analysis, their interrelationship is determined. It is theoretically based on the fact that the word Akqotal has undergone a number of sound changes and has acquired this appearance today. Alisher Navoi's thoughts about the "Iron Gate" used in the epic "Saddi Iskandari" are similar to the above toponyms.